2007
DOI: 10.32635/2176-9745.rbc.2007v53n3.1798
|View full text |Cite
|
Sign up to set email alerts
|

Marcadores Tumorais: Revisão de Literatura

Abstract: Os marcadores tumorais são macromoléculas presentes no tumor, no sangue ou em outros líquidos biológicos, cujo aparecimento e/ou alterações em suas concentrações estão relacionados com a gênese e o crescimento de células neoplásicas. Este trabalho apresenta uma revisão da literatura nacional e internacional sobre o papel dos marcadores tumorais no manejo clínico de pacientes com câncer, desde o auxílio no diagnóstico e estadiamento até a avaliação da resposta terapêutica, detecção de recidivas e prognóstico, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 46 publications
0
2
0
5
Order By: Relevance
“…Among all the examinations, 50% had been performed in the previous year, probably due to the predominance of individuals aged over 60 in the sample. 3 • In the Baixada Santista, a study conducted among 927 respondents aged 40 years or older showed that 56.5% of them had been tested for prostate-specific antigen at least once in their lifetimes. 16 The risk factors for development of prostate cancer include the following:…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among all the examinations, 50% had been performed in the previous year, probably due to the predominance of individuals aged over 60 in the sample. 3 • In the Baixada Santista, a study conducted among 927 respondents aged 40 years or older showed that 56.5% of them had been tested for prostate-specific antigen at least once in their lifetimes. 16 The risk factors for development of prostate cancer include the following:…”
Section: Discussionmentioning
confidence: 99%
“…1,2 The combination of prostate-specific antigen testing and digital rectal examination has been considered to be an effective approach, since 18% to 45% of tumors would not have been diagnosed, had one of these two methods not been performed. 3 The American Cancer Society advises that, among men whose life expectancy exceeds 10 years, screening should be done annually, through informed consent. This should be started at the age of 50 years for those at moderate risk; at the age of 45 for those at high risk (afro-descendants and individuals with a history of prostate cancer in first-degree family members at ages younger than 65 years); and at the age of 40 for those at very high risk (multiple family members diagnosed with prostate cancer before the age of 65).…”
mentioning
confidence: 99%
“…Os marcadores tumorais podem ser proteínas, hormônios, fragmentos de proteínas, enzimas e antígenos de superfície celular. Estes elementos podem ser encontrados no sangue, urina, fezes, tumores, fluidos corporais e outros tecidos (DE ALMEIDA, 2007).…”
unclassified
“…As buscar pelos marcadores são realizadas a partir da coleta de material biológico do individuo em questão, como forma de prevenção ou de auxilio ao diagnostico medico, e nesse material são realizados técnicas de imuno-histoquímica para qualificação e quantificação dos níveis de determinado marcador (CARAPEBA,2009). O marcador ideal a ser utilizado em uma pesquisa de câncer, deve ser sensível ao ponto de apresentar elevação em quase a totalidade das pessoas que possuem a presença de células neoplásicas, e por conseguinte esteja constantemente normal nas pessoas que não apresentam as mesmas, tendo assim alta especificidade e sensibilidade, outros atributos à um marcador ideal são; dosagem fácil, baixo custo, utilidade no diagnostico e monitorização do tratamento (DE ALMEIDA, 2007).…”
unclassified
“…Ese estudio posee el objetivo de analizar y discutir la importancia de los marcadores tumorales en el tratamiento y diagnostico del cáncer. Cada marcador tumoral tem um valor de referência determinados; taxas acima do valor de referência apresentados por pacientes devem ser investigados (1) .…”
unclassified